Investigation of nuclear structure near doubly magic 132Sn - Das Sangeeta; Gupta Arkabrata (EPJ Web of Conferences)
Large-basis shell-model calculations have been performed to investigate the excited states of 131,132Sn using a newly formulated cross-shell interaction. Recent expansions of the level schemes has provided valuable structural insights. A detailed comparison of excitation energies and electromagnetic transition rates between experimental data and theoretical predictions offers a deep understanding of these nuclei. While certain transitions align well with experimental data, others show discrepancies. This observed discrepancies in some cases points the scope of improvement of theoretical results, such as fine tuning certain ν − ν tbmes.